Poor mental health and sexual risk behaviours in Uganda: A cross-sectional population-based study - Allebeck Peter; Thorson Anna; Ashaba Schola; Rukundo Godfrey; Lundberg Patric; Östergren Per-Olof; Cantor-Graae Elizabeth (BMC, 2011)
Abstract Background Poor mental health predicts sexual risk behaviours in high-income countries, but little is known about this association in low-income settings in sub-Saharan Africa where HIV is prevalent. This study investigated whether depression, psychological distress and alcohol use are associated with sexual risk behaviours in young Ugandan adults. Method Household sampling was performed in two Ugandan districts, with 646 men and women aged 18-30 years recruited. Hopkins Symptoms Checklist-25 was used to assess the presence of depression and psychological distress. Alcohol use was assessed using a question about self-reported heavy-episodic drinking. Information on sexual risk behaviour was obtained concerning number of lifetime sexual partners, ongoing concurrent sexual relationships and condom use. Results Depression was associated with a greater number of lifetime partners and with having concurrent partners among women. Psychological distress was associated with a greater number of lifetime partners in both men and women and was marginally associated (p = 0.05) with having concurrent partners among women. Psychological distress was associated with inconsistent condom use among men. Alcohol use was associated with a greater number of lifetime partners and with having concurrent partners in both men and women, with particularly strong associations for both outcome measures found among women. Conclusion Poor mental health is associated with sexual risk behaviours in a low-income sub-Saharan African setting. HIV preventive interventions should consider including mental health and alcohol use reduction components into their intervention packages, in settings where depression, psychological distress and alcohol use are common.